2018
DOI: 10.1016/j.jagp.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Suicide Attempts and Unintended Death Among Those Transitioning From Prison to Community in Later Life

Abstract: Older re-entry veterans are at considerable risk of attempting suicide and dying by drug overdose or other accidental injury. This study highlights importance of prevention and intervention efforts targeting later-life prison-to-community care transitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 31 publications
1
13
0
1
Order By: Relevance
“…In an interview study with 124 prisoners aged 50+ years, Barry et al demonstrated that a past alcohol dependence and a poor self-rated health were associated with elevated suicidal ideation. Altogether, in their study, 22% of the older prisoners were showing current suicidal ideation and 12% were reporting active suicidal ideation (20).…”
Section: Introductionmentioning
confidence: 98%
“…In an interview study with 124 prisoners aged 50+ years, Barry et al demonstrated that a past alcohol dependence and a poor self-rated health were associated with elevated suicidal ideation. Altogether, in their study, 22% of the older prisoners were showing current suicidal ideation and 12% were reporting active suicidal ideation (20).…”
Section: Introductionmentioning
confidence: 98%
“…Study strengths include the comprehensive assessment of Veterans Justice Program services for over 5.4 million Veterans who were recent users of VHA care. In contrast, to our knowledge, the only other national study on justice involvement and suicide among Veteran VHA users was limited to Veterans aged 50 and older (Barry et al, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…One national study has examined suicide risks among formerly incarcerated Veterans. For Medicare‐eligible VHA‐using Veterans aged 50 and older who were incarcerated between 2012 and 2014, there was greater risk of suicide attempts among older Veterans with a criminal justice history as compared to never‐incarcerated Veterans (Barry et al, 2018). No significant differences were found with regard to suicide mortality.…”
mentioning
confidence: 99%
“…nach Verbüßung einer Freiheitsstrafe ein erhöhtes Suizidrisiko haben, legt einerseits das Vorhandensein individueller Risikofaktoren nahe. Auf der anderen Seite spricht besonders die hohe Suizidrate der Untersuchungsgefangenen, die in allen untersuchten Gefängnispopulationen festgestellt wurde, für das Einwirken institutionell-situativer Einflüsse auf das Suizidrisiko im Gefängnis [1][2][3][4].…”
Section: Hintergrundunclassified